1999
DOI: 10.1002/j.2161-1874.1999.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Supervision of Substance Abuse Counselors: Current and Preferred Practices

Abstract: A national survey of substance abuse counselors (N = 134) was conducted to learn their current and preferred supervision practices. Results are presented for the entire sample, as well as within-group comparisons based on counselor recovery status and education level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 15 publications
4
33
0
Order By: Relevance
“…Through the working alliance the supervisor uses social influence, confirmation, and acceptance to help the counselor perform better on the job and develop professionally. According to counselors, the most important aspects of ECS are receiving professional support, obtaining social support to reduce burnout, learning how to work with particular types of clients, learning specific counseling skills, and developing greater self-awareness (Culbreth, 1999;Usher & Borders, 1993). This is consistent with Powell and Brodsky's contention that another important aspect of ECS involves the clinical supervisor acting as a mentor for the counselor.…”
Section: Effective Clinical Supervision (Ecs) and Counselor Job Perfosupporting
confidence: 58%
“…Through the working alliance the supervisor uses social influence, confirmation, and acceptance to help the counselor perform better on the job and develop professionally. According to counselors, the most important aspects of ECS are receiving professional support, obtaining social support to reduce burnout, learning how to work with particular types of clients, learning specific counseling skills, and developing greater self-awareness (Culbreth, 1999;Usher & Borders, 1993). This is consistent with Powell and Brodsky's contention that another important aspect of ECS involves the clinical supervisor acting as a mentor for the counselor.…”
Section: Effective Clinical Supervision (Ecs) and Counselor Job Perfosupporting
confidence: 58%
“…This need is particularly important in the substance use treatment field in which there is a wide variability among the training and clinical experiences of treatment providers (Culbreth, 1999). Thus, it is encouraging to note that several efforts to establish such instruments have been undertaken with MI.…”
Section: Discussionmentioning
confidence: 99%
“…Culbreth and Cooper (2008) found that those who supervise SACs are frequently overworked, underpaid, have limited resources available, and receive minimal, if any, training. Many supervisors also lack a graduate education (Reeves, Culbreth, & Greene, 1997), and those who possess an advanced degree never receive formal training in supervision (Culbreth, 1999). Furthermore, licensing/certification boards in many states require little or no education or training in clinical supervision for one to be approved as a supervisor (Hoge, Migdole, Farkas, Punce, & Hunnicut, 2011), which suggests that any substance abuse treatment professional could serve in that role.…”
Section: Support For Supervisorsmentioning
confidence: 99%
“…Most in the addictions field recognize the essential role supervision plays in helping SACs become competent practitioners (Borders & Brown, 2005;Culbreth, 1999;Culbreth & Borders, 1998;Durham, 2003;Knudsen, Ducharme, & Roman, 2008;Powell & Brodsky, 2004;Remley & Herlihy, 2010;Vallance, 2004). Through the supervisory relationship, a more senior professional (supervisor) is tasked with guiding and promoting the competence of a more novice aspiring counselor (supervisee) by enhancing the supervisee's professional and ethical knowledge and skills (Borders & Brown, 2005;Powell & Brodsky, 2004;Toriello & Benshoff, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation